Development & validation of a health awareness booklet: “Reproductive health schemes for tribal women of Jharkhand” a study protocol - Rohit Raj; Jarina Begum; Syed Irfan Ali; Manasee Panda; Vani Lakshmi R (PLoS ONE, 2025)
In India, women of reproductive age constitute of 22.2% of the total population. In tribal areas there are disparity in maternal health care utilization, lack of accessibility to safe menstrual health, malnutrition, and low contraceptive usage. This research will aim to study the utilization of healthcare schemes among tribal reproductive-age groups in Jharkhand. Based on the findings a health awareness booklet will be developed and validated. This study can contribute in designing effective interventions and policies that cater to the specific needs of tribal communities, ultimately improving their access to quality healthcare services. The proposed research will follow the sequential explanatory approach, conducted in two phases. Phase one will assess the knowledge, attitude, and practices of reproductive healthcare schemes among tribal women. We will also explore the facilitators and challenges in the provision of schemes from different stakeholder perspectives. Phase two the development and validation of the awareness booklet for the tribal women will be done. The sampling frame will consist of adolescent girls (10–19 years) and reproductive-age group women (15–49 years), from the tribal communities in East Singhbhum district of Jharkhand. Qualitative aspect will include study participants such as Block Program Manager, Block Trainer, Accredited Social Health Activist (ASHA), Auxiliary Nurse Midwifery (ANM), Aanganwadi Workers (AWW), Medical Officer, Village leaders, and Tribal Women. Research on the knowledge, attitude, and practices towards health coverage schemes in tribal regions of India is essential for addressing health disparities. Improving awareness and understanding, overcoming attitudinal barriers, informing policy development, and promoting equity and social justice in healthcare are some of the disparities. This study will help to increase in knowledge, awareness, and attitude for reproductive age group tribal women health coverage schemes. Trial registration Clinical Trial Registry-India (CTRI) CTRI/2024/03/063824